EFFECT OF WORK ENVIRONMENT AND WORKLOAD ON EMPLOYEES’ PERFORMANCE IN GOVERNMENT TEACHING HOSPITALS IN NORTH CENTRAL NIGERIA - Emmanuel, Nkechi Grace; Zwingina, Christy; Shittu, Olabisi (African Journal of Social and Behavioural Sciences, 2025)
A good work environment and a fair amount of work are important for employees to do their best. Having a reasonable workload prevents stress and burnout, making it easier to do quality work without feeling too tired or pressured. This study examines the effect of work environment and workload on employees’ performance. Government Teaching Hospitals in North Central Nigeria was chosen because as public healthcare institutions, they have a high volume of patients’ base from every part of the country especially for the highly specialized services, operates in unique environment, and are generic in structure and administration. A cross-sectional research design was adopted for this study with a population of 7293 and a sample size of 417 staff. Data were collected through a questionnaire and analysed using the Partial Least Structural Equation Model (PLS-.SEM). The study found that while workload had a positive and significant effect on employee performance, the work environment had no meaningful impact on employee performance. The study concluded that the work environment does not enhance employee performance; workload led to improvement in employee performance. The study recommends that the management of Government Teaching Hospitals should improve workplace conditions and maintain a balanced workload for optimal performance.